Treating Acute Insomnia: A Randomized Controlled Trial of a “Single-Shot” of Cognitive Behavioral Therapy for Insomnia - Ellis, Jason G.; Cushing, Toby; Germain, Anne (Sleep (New York, N.Y.), 2015)
Despite considerable evidence supporting cognitive behavioral therapy for insomnia (CBT-I) for chronic insomnia, it remains untested within the context of acute insomnia. This study examined the efficacy of a single session of CBT-I, with an accompanying self-help pamphlet, for individuals with acute insomnia. A pragmatic parallel group randomized controlled trial. Community. Forty adults (mean age 32.9 ± 13.72 y) with Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) defined insomnia disorder, except a self-reported duration of less than 3 mo (i.e., acute insomnia), who reported no previous exposure to CBT-I and were not currently taking medication for sleep. A single 60- to 70-min session of CBT-I (n = 20), with an accompanying self-help pamphlet, or wait list control group (n = 20). All subjects were offered a full individual course of CBT-I on completion of the study, regardless of group allocation. Subjects completed sleep diaries and the Insomnia Severity Index (ISI) pretreatment and 1 mo following treatment. There were no between-group differences on baseline ISI scores or subjective sleep continuity. The intervention group reported significantly lower ISI scores than controls (t(38) 2.24, P < 0.05) at follow-up. Further, using proposed ISI scores for identifying insomnia caseness (i.e., ≥ 10), 60% of those in the CBT-I group had remitted by 1 mo compared to 15% of those in the control group. This single session of cognitive behavioral therapy for insomnia (CBT-I) is sufficiently efficacious for a significant proportion of those with acute insomnia. The results are discussed in terms of integrating this brief form of CBT-I into the "stepped care" model of insomnia. Testing the efficacy of an early intervention for acute insomnia (SRCTN05891695) http://www.controlled-trials.com/ISRCTN05891695.